The Development of Human Embryos from a Modern Medical Perspective and the Qurʼān: A Bibliometric Analysis - Luqmi, Fitra Zahrotul; Kesuma, Aghesna Rahmatika; Nabilla; Eduard (Universitas Islam Negeri Raden Intan Lampung, 2026)
Human embryonic development constitutes one of the most intensively studied domains in biomedical science; however, interdisciplinary engagement connecting modern embryology with Qur'ānic descriptions of human creation remains markedly underrepresented in the indexed literature. This study presents a comprehensive bibliometric analysis of scientific publications on human embryonic development (2016–2026), integrating modern medical perspectives with Qur'ānic teachings to map scholarly output, identify dominant themes, and delineate gaps in interdisciplinary inquiry. A systematic search of the Scopus database using the query